Accuracy and Coverage of Diagnosis and Procedural Coding of Severely Injured Patients in the Finnish Hospital Discharge Register: Comparison to Patient Files and the Helsinki Trauma Registry. (September 2017) - Heinänen, M.; Brinck, T.; Handolin, L.; Mattila, V. M.; Söderlund, T.
Background and Aims: The Finnish Hospital Discharge Register data are frequently used for research purposes. The Finnish Hospital Discharge Register has shown excellent validity in single injuries or disease groups, but no studies have assessed patients with multiple trauma diagnoses. We aimed to evaluate the accuracy and coverage of the Finnish Hospital Discharge Register but at the same time validate the data of the trauma registry of the Helsinki University Hospital's Trauma Unit. Materials and Methods: We assessed the accuracy and coverage of the Finnish Hospital Discharge Register data by comparing them to the original patient files and trauma registry files from the trauma registry of the Helsinki University Hospital's Trauma Unit. We identified a baseline cohort of patients with severe thorax injury from the trauma registry of the Helsinki University Hospital's Trauma Unit of 2013 (sample of 107 patients). We hypothesized that the Finnish Hospital Discharge Register would lack valuable information about these patients. Results: Using patient files, we identified 965 trauma diagnoses in these 107 patients. From the Finnish Hospital Discharge Register, we identified 632 (65.5%) diagnoses and from the trauma registry of the Helsinki University Hospital's Trauma Unit, 924 (95.8%) diagnoses. A total of 170 (17.6%) trauma diagnoses were missing from the Finnish Hospital Discharge Register data and 41 (4.2%) from the trauma registry of the Helsinki University Hospital's Trauma Unit data. The coverage and accuracy of diagnoses in the Finnish Hospital Discharge Register were 65.5% (95% confidence interval: 62.5%–68.5%) and 73.8% (95% confidence interval: 70.4%–77.2%), respectively, and for the trauma registry of the Helsinki University Hospital's Trauma Unit, 95.8% (95% confidence interval: 94.5%–97.0%) and 97.6% (95% confidence interval: 96.7%–98.6%), respectively. According to patient records, these patients were subjects in 249 operations. We identified 40 (16.1%) missing operation codes from the Finnish Hospital Discharge Register and 19 (7.6%) from the trauma registry of the Helsinki University Hospital's Trauma Unit. Conclusion: The validity of the Finnish Hospital Discharge Register data is unsatisfactory in terms of the accuracy and coverage of diagnoses in patients with multiple trauma diagnoses. Procedural codes provide greater accuracy. We found the coverage and accuracy of the trauma registry of the Helsinki University Hospital's Trauma Unit to be excellent. Therefore, a special trauma registry, such as the trauma registry of the Helsinki University Hospital's Trauma Unit, provides much more accurate data and should be the preferred registry when extracting data for research or for administrative use, such as resource prioritizing.